Modification of surface layers by high energy treatment - M. N. Vereschagin; S. N. Tselueva; M. Yu. Tseluev (Литьë и металлургия)
Exposure to laser radiation leads to a change in the temperature field of the substance being treated. The nature of heating, which is determined by the rate of change of temperature, temperature gradients, the time to reach the temperatures of structural and phase transitions, is different depending on the properties of the material being processed and the processing conditions.When modifying the surface layers by high-energy processing by changing the power and time of exposure to laser radiation, you can get a wide range of structural states of the treated surface areas of the material.It is shown that the shape of TVP diagrams and cooling curves of precision alloys on the surface of a two-layer metal system after heating them with laser radiation are determined by the competition of two processes acting in opposite directions: an increase in the driving force of the crystallization process with an increase in supercooling and a decrease in the surface of atoms.The method of surface modification by moving laser radiation allows to obtain amorphous functional layers of precision alloys on the surface of metal products.